Reminiscences of the anti-Japanese guerillas. [With contribs of Lim Chun Chu, O Baek Ryong, Pak Sung Chul a.o.] (Foreign Languages Publishing House, 1968)
The Party History Institute under the C.C. of the Workers' Party of Korea.